2012
DOI: 10.1088/1674-1056/21/8/087501
|View full text |Cite
|
Sign up to set email alerts
|

Wiedemann effect of Fe—Ga based magnetostrictive wires

Abstract: (Fe83Ga17)98Cr2 wires each with a diameter of 0.7 mm are prepared by hot swaging and warm drawing from the casting rods directly, because the ductility of Fe83Ga17 alloy is improved by adding Cr element. The Wiedemann twists and dependences on magnetostrictions of Fe83Ga17 and (Fe83Ga17)98Cr2 wires are investigated. The largest observed Wiedemann twists of 245 s·cm−1 and 182 s·cm−1 are detected in the annealed Fe83Ga17 and (Fe83Ga17)98Cr2 wires, respectively. The magnetostrictions of the annealed Fe83Ga17 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The characteristic accords remarkably well with results shown in earlier works. 29) In addition, it is worth to note that the twist angle could further increase with a higher H c than 1300 A/m, as shown in Fig. 5(b).…”
Section: Resultsmentioning
confidence: 82%
“…The characteristic accords remarkably well with results shown in earlier works. 29) In addition, it is worth to note that the twist angle could further increase with a higher H c than 1300 A/m, as shown in Fig. 5(b).…”
Section: Resultsmentioning
confidence: 82%
“…5 Li et al have found that magnetostriction of the waveguide wire is an important factor for the Wiedemann effect, and that the Wiedemann torsion increases with magnetostriction. 6 The signal amplitude of Fe-Ga waveguide wire displacement sensor is higher than that of Fe-Ni waveguide wire displacement sensor. 7 In the previous work, the output voltage model of magnetostrictive displacement sensor under the action of spiral magnetic field was established.…”
Section: Introductionmentioning
confidence: 87%
“…In fact, the Wiedemann twist angle produced by the waveguide wire is related to the magnetostriction of the waveguide wire. 6,9 Therefore, it is interesting to investigate the relationship between the output voltage of magnetostrictive displacement sensor and the magnetostriction of the waveguide.…”
Section: Introductionmentioning
confidence: 99%
“…11 The Galfenol ring-shaped sample made by stacking several wires with the same internal and external meets the requirement of IEC 60404-4 and IEC 60404-6 standards. Ring-shaped sample was chosen to avoid demagnetizing effects.…”
Section: Methodsmentioning
confidence: 97%